Microbial community changes during the mechanized production of light aroma Xiaoqu baijiu. Issue 1 (1st January 2021) - Hu, Yuanliang; Wang, Luyao; Zhang, Zongjie; Yang, Qiang; Chen, Shenxi; Zhang, Long; Xia, Xian; Tu, Junming; Liang, Yunxiang; Zhao, Shumiao
Abstract: Multi-microorganisms mixed fermentation is the main characteristic of Chinese baijiu brewing. In this study, plate culture and high-throughput sequencing were used to investigate the changes in microbial community during baijiu brewing. The results revealed that fungi accounted for the largest number of culturable microorganisms, followed by bacteria and molds. The diversity of bacteria and fungi first increased and then decreased, before increasing slightly at the late stage. Most microbial species came from the environment or raw materials, and the microbial community changed greatly during fermentation; thus, the dominant microorganisms in the starter might not be the dominant organisms during fermentation. The bacterial composition changed in a certain pattern, and the core microbes were lactic acid bacteria and Acetobacter pasteurianus . The composition of each genus was relatively uniform at the early stage, while Lactobacillus spp. were dominant at the late stage. Among them, Lactobacillus sp., which ranked first, had low initial abundance, before reaching 63.7% at the end. Four fungi, Saccharomyces cerevisiae, Wickerhamomyces anomalus, Aspergillus sp. and Rhizopus oryzae, were dominant, accounting for 74.6%–93.6% of the species present, among which the first two accounted for 50.3%–81.2%. This study provides a basis for the mechanized production of Xiaoqu baijiu .